Elevational gradients in phylogenetic structure of ant communities reveal the interplay of biotic and abiotic constraints on diversity - Macháč, Antonín (Jihočeská univerzita, 2011)
Incorporating information on species? phylogeny into the framework of conventional community ecology, we illustrate that ant communities situated in lowlands are primarily structured by interspecific competition. In contrast, highland communities are formed by habitat filtering on phylogenetically conserved temperature tolerances. In sum, our study highlights the potential role of niche constraints, environmental temperature, and competition in shaping broad-scale diversity gradients.
Elevational gradients in phylogenetic structure of ant communities reveal the interplay of biotic and abiotic constraints on diversity
Keywords: community structure; phylogeny; biodiversity; elevational gradients; community structure; phylogeny; biodiversity; elevational gradients